EKSISTENSI DIKIE PANO SEBAGAI MEDIA DAKWAH DI KABUPATEN PASAMAN - Genta Haramain (Communicative : Jurnal Dakwah dan Komunikasi, 2024)
The spread of Islam in Indonesia carried out by missionaries is carried out through several methods, one of which is using voice communication media, namely the art of music. In the Minangkabau area, Islamic Sharia is the foundation and reference of the socio-cultural order so that it unites and forms local wisdom and one of the forms of cultural products that is influenced by Islam is the art of Dikie Pano in Pasaman Regency. West Sumatra Province it self also has an art similar to Dikie Pano which is spread to several other regions with different names such as Dikie Mundam Luhak Tanahdata, Dikia Rabano Ampek Angkek and Dikia Mauluik in Ulakan Pariaman. Dikie Pano in Pasaman Regency is still extremist to this day and the performances are always held at cultural rituals and celebrations of holidays in Pasaman Regency, for example the celebration of the Equatorial Culmination Point, and the Pasaman Birthday. In Dikie Pano's performance material , there are Islamic syiar values presented with chants and poems that contain sharia elements and are ringed with rhythmic melodies from the tambourine percussion instrument called Pano. This paper explains the Art of Music Dikie Pano as an effective means for da'wah whose research is carried out with an ethnographic approach and using descriptive analysis. Results In the study, Dikie Pano is a combination of Islamic, Minagkabau, and Arabic elements which has the main target of spreading Islamic religious teachings. It is said to be a da'wah medium because Dikie Pano in his performance uses percussion instruments in the form of tambourine and singing using lyrics in the form of prayers taken from the Qur'an and verses in the Book of Barzanji by the Arabic writer Al Barzanji, so that through the performance it is effective as a means of conveying the teachings of Islam.